Analisis Pengaruh Faktor-Faktor Resiko terhadap Kinerja Mutu PT. Mega PersadaIndonesia (Studi Kasus Proyek Daswin Office Tower) - Resapugar; Nurlela (Jurnal Manajemen, 2021)
Risk is an uncertainty or mismatch which will affect quality performance and it can create losses of the cost, time and quality of work. This research aims to know the impact of risk factors to quality performance at PT. Mega Persada Indonesia at Daswin Office Tower Project. Risk factors that cause quality failures, such as risk factors of the aspects of human resources, engineering and review, materials and equipment. Project quality performance can be measured to the products produced and services provided. This research used quantitative methods with data collection techniques based on observations, interviews, questionnaires, and documentation. The number of respondents sampled used in this research were 44 respondents. To analize data the researcher used descriptive analysis and statistical tests. Based on simultaneous testing, the relationship strength level of the independent variable to the dependent variable of –0.938 means very strong and opposite direction, the contribution of the independent variable to the dependent variable of 87.9%, while the remaining 12.10% is affected by other variables not researched in this study. The test results F arithmetic (97,110) > F table (4.30) and the significance value (0,000) ≤ α (0.01), it indicates there is a significant impact simultaneously between risk factors aspects of human resources, engineering and review, material and equipment to quality performance at PT. Mega Persada Indonesia at Daswin Office Tower Project.